Organizacja i zasady działania systemu informacji marketingowych w przedsiębiorstwie eksportującym - Malinowski, Andrzej (Wydział Prawa i Administracji UAM, 1979)
The author is continuing consideration on marketing information system in an exporting enterpise. Proposal of organizing marketing information system presented in the article takes into account practical differences between spheres of production and turn-over in the Polish foreign trade system. Furthermore, the majority of national exporting enterprises in organized as a conglomeration of branch institutions possessing independence to a certain degree. The proposed concept of system organization avails itself of principles of centralization as we)ll as de-centralization informative activity. It means that the whole of actions in the sphere of marketing information, indispensable fol creation and proper realization of a certain concept of exporting enterprise management, should be concentrated in a proper functional service. In this way, the system's activity is based on central (forced) flow of marketing information what eliminates it's casualty. Other information activities (collecting, initial processing, as well as information transmission) are de-concentrated. They belong to competence of particular enterprise units. Such solution is fully concordant with the modern management model, in which only strategic decisions are centralized while decisions in operative actions are decentralized. The principle of marketing information system functioning presented in the article are of a model character. The detailed system's organization and functioning is then dependent on: real information needs of an exporting enterprise, existing organization, workers qualifications etc. The model approach should then facilitate for organization of marketing information system as well as for elaboration of principles of it's functioning adequate for a given enterprise. That was the assessment in the article.
Organization and Principles of Marketing Information System in an Exporting Enterprise
Keywords: UAM